Incorporación de la responsabilidad autónoma de las personas jurídicas en el dictamen sobre el nuevo Código Penal: ¿ahora sí necesito un criminal compliance? - Ruiz Baltazar, Carmen; Palomino Ramírez, Walter (Pontificia Universidad Católica del Perú, 2015)
Currently, different legal systems are starting to demand criminal responsibility of corporate bodies. The Opinion on the New Criminal Code, prepared by the Justice and Human Rights Commission of the Congress of the Republic of Peru, follows this trend, proposing an exemption from liability in case the corporate body counts with a criminal compliance.Given this situation, in this article, the authors answer the arising questions: what does criminal compliance stands for? What are the accessory consequences of the criminal liability of corporate bodies in our current legislation? What are the novelties that the Opinion on the New Criminal Code introduces?

Actualmente, diversas legislaciones están comenzando a exigir la responsabilidad penal de las personas jurídicas. El Dictamen del Nuevo Código Penal, elaborado por la Comisión de Justicia y Derechos Humanos del Congreso de la República, sigue esta corriente, planteando la excepción de responsabilidad en el caso de contar con un criminal compliance.Frente a tal realidad, los autores responden a las cuestiones que surgen: ¿en qué consiste el criminal compliance? ¿Cuáles son las consecuencias accesorias de la responsabilidad penal de las personas jurídicas en nuestra actual legislación? ¿Qué novedades trae la propuesta del Dictamen del Nuevo Código Penal?
Incorporation of the autonomous liability of corporate bodies in the opinion on the new Criminal Code: do I need now a criminal compliance?
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01